"Wolff's Philosophical Anarchism - An Analysis" - Tan, Kuan Aw (1980)
This thesis begins with an Introduction which briefly describes the two basic theses of Wolff's position. Firstly, Wolff argues that political authority cannot be justified on moral grounds because there is an irresolvable conflict between political authority and autonomy - man's fundamental moral duty. Secondly, he argues that no political theory can succeed in resolving this problem and in particular classical democratic theory has failed to do so. Hence Wolff concludes that political authority must be rejected and anarchism is the only conclusion left for a rational man.